Citra Merek, Kualitas Produk, Promosi, Kualitas Pelayanan dan Kepuasan Konsumen - Nasrul Efendi; Sugianta Ovinus Ginting; Jimmy Halim (Universitas Musamus,Merauke,Papua, 2020)
This writing aims to analyze and examine the effect of brand image, product quality, promotion and service quality on consumer satisfaction of telurgulungku in fun street Adam Malik. This type of research uses quantitative research methods with descriptive and associative approaches. The data model analysis used is multiple linear regression. The results showed that brand image, product quality, promotion and service quality had a significant effect on customer satisfaction partially or simultaneously. The brand image that is formed by my telurgulungku will well affect consumer satisfaction and in making Telurgulungku products pay attention to the quality of the product produced by providing an identity or characteristics compared to similar products on the market to consumers in terms of texture, taste, distinctive legit aroma and hygienic packaging. which guarantees the safety and cleanliness of the product when consumed by consumers. One of the ways to promote Telurgulungku is carried out by means of direct selling or a method of selling certain goods and services to consumers by face-to-face outside fixed shop locations by the marketing network. This shows that the influence of brand image, product quality, promotion and service quality is still effective in its use in world marketing in the present era.